Juridis Implication of Government Regulation No. 1 of 2017 on Mineral and Coal Mining Business Activity by Foreign Investor - Putu Edgar Tanaya (Sociological Jurisprudence Journal, 2018)
The purpose of this research is to know and understand the regulation of mineral and coal mining business implementation conducted by foreign investors before the birth of Rule Number 1 Year 2017 and to know and understand the implication of the birth of Regulation No. 1 of 2017 is hurt with the aim of the state. In this research, to reach the objective, normative research method with regulatory approach is applied by reviewing the laws and regulations related to research and case approach related to the divestment of mining business by foreign investors. The conclusion yields two conclusions. The first conclusion is the regulation of the implementation of mineral and coal business activities prior to the issuance of Government Regulation No. 1 of 2017 is regulated in several laws and regulations which have two weak points. The first concerns the regulation of inconsistent divestment shares and both mechanisms of work contracts that are detrimental to the Government of Indonesia. the second conclusion, the issuance of Government Regulation No. 1 of 2017 confirms the number of divestment shares and changes in working contract patterns to mining business permits maximizing the realization of welfare for all Indonesian people.